Notes on research into some aspects of stall-warning devices - Bethwaite, C. F.; Langley, R. A. (College of Aeronautics, Cranfield, 1953)
The problems of detecting and indicating an approaching stall have been investigated in flight on an “Anson” aircraft. A lower-surface flap near the leading-edge of the wing detects the approaching stall at a speed which depends critically on the length of the flap and on its location, but the margin of warning speed over stalling-speed is reasonably independent of landing-flap position and throttle setting. Continues …